Design, Synthesis, and the Biological Evaluation of Some New Fused Thiazolotriazine Derivatives: Pharmaceutical sciences- Pharmaceutical Chemistry - Thabet, Hamdy K H.; Imran, Mohd; Alaqel, Saleh; Hamdy Helal, Mohamed; Abida (International Journal of Life Science and Pharma Research, 2024)
Thiazolotriazine is an essential medicinal chemistry molecule due to its biological properties, particularly antifungalactivity. Antifungal drug resistance is rising worldwide, necessitating the development of innovative, safer, and more effectiveantifungals. This study intended to uncover safer and more effective thiazolotriazine antifungals. ProTox II software was employedto forecast the toxicity of the designed thiazolotriazines. The pharmacokinetic parameters were calculated using the Swiss-ADMEdatabase. The Molecular Operating Environment software (2019.0102 version) was employed for the docking studies utilizing 14-α-demethylase protein (PDB ID: 3LD6). Compounds 4c, 4d, and 4e were prepared and evaluated for in vitro antifungal activity.The computational studies revealed compounds 4a, 4b, 5b, 5c, 6b, 6c and 6d as carcinogenic; 4a, 4b, 4c, 4d and 4e demonstratedbetter pharmacokinetic behaviour; and docking results of 4c, 4d, and 4e were superior than fluconazole (FLU). The moleculardocking studies establish 4c, 4d, and 4e as SDM inhibitors, suggesting a mechanism similar to FLU and ketoconazole (KET). Theantifungal activity evaluation revealed 4d (MIC = 6.25 μg/ml) as a more potent antifungal agent than KET (MIC = 12.5 μg/ml) andFLU (MIC = 12.5 μg/ml). Compounds 4c and 4e showed equal antifungal activity to KET (MIC = 12.5 μg/ml) and FLU (MIC = 12.5μg/ml). Compounds 4c, 4d, and 4e displayed encouraging antifungal activity with a favorable safety profile. Assessing the broadspectrum of 4c, 4d, and 4e against various pathogenic fungi, including resistant forms, is recommended.